Genetic Variability in Balkan Paleoendemic Resurrection Plants Ramonda serbica and R. nathaliae Across Their Range and in the Zone of Sympatry - Lazarević, Maja; Siljak-Yakovlev, Sonja; Sanino, Agathe; Niketić, Marjan; Lamy, Françoise; Hinsinger, Damien D.; Tomović, Gordana; Stevanović, Branka; Stevanović, Vladimir; Robert, Thierry (Frontiers in Plant Science, 2022)
The genus Ramonda includes three Paleoendemic and Tertiary relict species that survived in refugial habitats of the Balkan Peninsula (R. nathaliae and R. serbica) and the Iberian Peninsula (R. myconi). They are all "resurrection plants", a rare phenomenon among flowering plants in Europe. Ramonda myconi and R. nathaliae are diploids (2n=2x=48), while R. serbica is a hexaploid (2n=6x=144). The two Balkan species occur in syntopy in only two localities in eastern Serbia, where tetraploid potential hybrids (2n=4x=96) were found. This observation raised questions about the existence of gene flow between the two species and, more generally, about the evolutionary processes shaping their genetic diversity. To address this question, genetic markers (AFLP) and an estimate of genome size variation were used in a much larger sample and at a larger geographic scale than previously. The combination of AFLP markers and genome size results suggested ongoing processes of interspecific and interploidy hybridization in the two syntopies. The data also showed that interspecific gene flow was strictly confined to syntopies. Elsewhere, both Ramonda species were characterized by low genetic diversity within populations and high population differentiation. This is consistent with the fact that the two species are highly fragmented into small and isolated populations, likely a consequence of their postglacial history. Within syntopies, enormous variability in cytotypes was observed, exceeding most reported cases of mixed ploidy in complex plant species (from 2x to > 8x). The AFLP profiles of non-canonical ploidy levels indicated a diversity of origin pathways and that backcrosses probably occur between tetraploid interspecific hybrids and parental species. The question arises whether this diversity of cytotypes corresponds to a transient situation. If not, the question arises as to the genetic and ecological mechanisms that allow this diversity to be maintained over time.